2020
DOI: 10.14309/ctg.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Very Low Calorie Diet to Achieve a Sustainable 10% Weight Loss in Patients With Nonalcoholic Fatty Liver Disease

Abstract: INTRODUCTION: Nonalcoholic fatty liver disease (NAFLD) is the most common liver condition worldwide. A weight loss goal of ≥10% is the recommended treatment for NAFLD; however, only a minority of patients achieve this level of weight reduction with standard dietary approaches. This study aimed to determine whether a very low calorie diet (VLCD) is an acceptable and feasible therapy to achieve and maintain a ≥10% weight loss in patients with clinically significant NAFLD. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 42 publications
1
52
0
2
Order By: Relevance
“…These baseline characteristics closely matched those of the whole sample of patients taking part in the LED feasibility study, as confirmed by statistical analysis, showing good representation. 13 The qualitative data collected from patients who took part in the LED intervention generated six themes and four subthemes that highlighted a number of factors associated with uptake, engagement and adherence. A summary of themes and subthemes is presented as figure 1, and table 2 presents a narrative summary of findings in relation to each theme and subtheme.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These baseline characteristics closely matched those of the whole sample of patients taking part in the LED feasibility study, as confirmed by statistical analysis, showing good representation. 13 The qualitative data collected from patients who took part in the LED intervention generated six themes and four subthemes that highlighted a number of factors associated with uptake, engagement and adherence. A summary of themes and subthemes is presented as figure 1, and table 2 presents a narrative summary of findings in relation to each theme and subtheme.…”
Section: Resultsmentioning
confidence: 99%
“…12 Despite the LED approach being used to actively reduce liver volume and fat prior to bariatric surgery since 2004, it had never been formally assessed as a treatment strategy for NAFLD until recently. [13][14][15] Our study assessed the acceptability and feasibility of delivering a LED to patients with clinically significant NAFLD and found that it is a potential treatment option, with 34% of patients maintaining >10% weight loss at 9-month follow-up and 51% and 68% maintaining >7% and >5%, respectively. 13 A recent systematic review synthesised qualitative studies investigating participants' experiences of undertaking a Very low energy diet (VLED) achieved using total meal replacement products.…”
Section: Summary Boxmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of multifaceted behavioral weight management programs has been widely described in the literature [18][19][20][21]. However, much of the available evidence is derived from clinical trials that are conducted in a controlled setting under the supervision of experienced researchers at academic institutions.…”
Section: Discussionmentioning
confidence: 99%